Trends in Arctic summer cloud variability from 2000 to 2022 and the potential causes - Zhang, Haotian; Zhao, Chuanfeng; Chen, Annan; Yang, Yikun; Li, Jiefeng; Zhao, Xin; Zhou, Yue; Fan, Hao (Science China. Earth sciences, 2025)
Climate change in the Arctic serves as a pivotal indicator of alterations in the global climate system, with clouds playing an essential role in regulating the surface radiative energy balance in the Arctic. Elucidating the patterns of Arctic cloud variability and the underlying mechanisms is of paramount scientific importance for understanding Arctic climate change. Spatiotemporal analysis of Arctic cloud characteristics reveals that since the onset of the 21st century, low clouds have predominantly comprised the Arctic summer cloud fraction (approximately 60%), followed by middle clouds (approximately 30%). The total-cloud fraction has exhibited a marked increasing trend, especially in the Beaufort Sea and Chukchi Sea (0.45%/yr). An attribution analysis suggests that the changes in the Arctic cloud fraction are chiefly driven by trends in two atmospheric circulation modes: The Arctic Oscillation (AO) and the Arctic dipole anomaly (DA). During positive phases of the AO, the cloud fraction increases across all Arctic basins. Conversely, in the positive phases of the DA, the cloud fraction decreases in the Beaufort Sea, Chukchi Sea, and Greenland Sea, whereas it increases in the East Siberian Sea, Kara Sea, and Barents Sea, indicating an “east-west” dipole distribution. Since 2000, the AO has been on an upward trend, whereas the DA has been declining. The combined effect of these two modes has resulted in a significant increase in the cloud fraction within the Beaufort Sea region. Further examination of cloud radiative effects indicates that an increase in the cloud fraction intensifies both longwave warming and shortwave cooling effects, leading to an overall net negative radiative effect. Analyzing the long-term trends in Arctic summer clouds enhances our comprehension of Arctic climate change.